2018
DOI: 10.1007/s10545-018-0244-6
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 as a biomarker for long‐term complications in organic acidemias

Abstract: This study demonstrates the potential role of FGF-21 as a biomarker for long-term complications in classical organic acidemias, attributed to mitochondrial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 43 publications
7
36
0
Order By: Relevance
“…Consistent with previous studies, 8,9 we also found that FGF21 correlated with the disease burden, although the categorical clinical findings we considered to evaluate the disease burden were different from other studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, 8,9 we also found that FGF21 correlated with the disease burden, although the categorical clinical findings we considered to evaluate the disease burden were different from other studies.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, fibroblast growth factor 21 (FGF21), a peptide hormone playing a key role in whole-body energy homeostasis and associated with mitochondrial dysfunction, 7 has been shown to be as a highly predictive biomarker for long-term complications in PA and MMA. 8,9 Thus far, MCA has been mainly considered a helpful biomarker for diagnosis of inherited disorders of propionate metabolism, but its utility in guiding the adjustment of treatment regimens and in predicting the metabolic status still needs to be established, with only a few works reporting data on urine/plasma MCA in the follow-up of PA and MMA. 5,[10][11][12][13][14][15] In this study, we have prospectively evaluated plasma concentrations of MCA and its correlations with primary and secondary biomarkers, including FGF21, in a large series of PA and MMA patients, on standard treatment and/or after transplantation, to explore the potential contribution of MCA quantification in the long-term management of organic acidemias.…”
Section: Introductionmentioning
confidence: 99%
“…Of great importance to the consideration of FGF21 as a hepatic biomarker for MMA patients, where renal disease directly influences the serum levels of methylmalonic acid, FGF21 concentrations did not correlate with renal disease indices, including creatinine, cystatin C, and estimated GFR, suggesting that circulating FGF21 will be a particularly useful biomarker to track hepatic mitochondrial dysfunction and response to MUT replacement therapies, independent of kidney function. A study published while the current work was under review further validates the correlations between plasma FGF21 and disease severity and lack of strong association with renal dysfunction in MMA patients (68). Because FGF21 is a pancreatic secretagogue (69) and increases bone loss (70,71), additional roles in the pathophysiology of MMA mediated by FGF21, such as the propensity toward pancreatitis and low bone density, seem likely.…”
Section: Discussionsupporting
confidence: 63%
“…Mitochondrial dysfunction plays an important role in the pathophysiology of MMA, and FGF‐21 is a biomarker for mitochondrial dysfunction. Clearly increased FGF‐21 levels have been described in MMA . We confirmed the severe initial decrease of FGF‐21 after transplantation as recently reported by Manoli et al in our two case reports.…”
Section: Discussionsupporting
confidence: 92%
“…Clearly increased FGF-21 levels have been described in MMA. 22,[39][40][41][42] We confirmed the severe initial decrease of FGF-21 after transplantation as recently reported by Manoli et al 43 in our two case reports. However, we also showed an increase in FGF-21 plasma levels in case 1 at the time of neurological symptoms due to CNI-induced PRES with a decrease in FGF-21 with improvement of symptoms and brain MRI-scan findings.…”
Section: Outcomesupporting
confidence: 91%